The prediction of all-around event final score based on d and e score factors in women's artistic gymnastics - Atikovic, A.; Kamenjaševic, E. (Science of Gymnastics Journal, 2021)
In the present study, we try to establish whether specific disciplines in women`s artistic gymnastics are equal and should the applicable Code of Points (COP) be revised in terms of point standardization on apparatus. Our sample included all-around senior female gymnasts who participated in the qualification (C-I) competitions from 2009 to 2019. The aim of our research was to determine the impact of individual apparatus D and E score in women's artistic gymnastic in relation to the final result of all-around event. The age among seniors rise from 2009 to 2019 for 1.88 years. In our analysis, we have found that the results achieved on each apparatus were significantly different. The average final scores on vault were significantly higher than on all other apparatus. Significant predictors of all-around success seem to be uneven bars D and E scores and balance beam E score. It was interesting to observe that the vault, balance beam and floor D scores were not significant predictors. Coaches can use the results from this research in their planning of preparation tactics for gymnasts in all-around, team and apparatus competitions.